The Actuality of the Council of Nicaea - Getcha, Job (The ecumenical review, 2023)
The year 2025 will mark the 1700th anniversary of the First Ecumenical Council, the Council of Nicaea, which initiated a new chapter in the history of the Christian Church. The World Council of Churches is planning to organize a World Conference on Faith and Order to celebrate this anniversary and to reflect on the transmission of the apostolic faith today. This conference is not intended to study the history of the council nor to study its theology, but rather to reflect on what “visible unity” means to different Christian churches and how Christians can collectively promote, preach, and live the apostolic faith today in the context of many contemporary challenges, such as secularization and religious pluralism. In this perspective, the present article reflects on the actuality of the Council of Nicaea and how it still ought to be considered as normative for the Christians of the 21st century.